Allopathic (MD) and Osteopathic (DO) Performance on the American Board of Physical Medicine and Rehabilitation Initial Certifying Examinations. Issue 9 (27th January 2020) - Sliwa, James A.; Raddatz, Mikaela M.; Kinney, Carolyn L.; Clark, Gary; Robinson, Lawrence
Abstract : Background: Osteopathic physicians (DOs) represent over 30% of residents in allopathic (MD) Accreditation Council for Graduate Medical Education (ACGME) accredited physical medicine and rehabilitation (PM&R) training programs. However, some have questioned the quality of osteopathic medical school training and the graduates of osteopathic medical schools. The performance of osteopathic physicians in allopathic PM&R training programs has not been assessed. Objective: To compare allopathic (MD) and osteopathic (DO) physician performance on American Board of Physical Medicine and Rehabilitation (ABPMR) initial certifying examinations. Design: Retrospective cross‐sectional study. Setting: Board‐eligible PM&R physicians. Participants: MDs and DOs who completed an allopathic ACGME‐accredited PM&R residency training program. Methods: MD and DO pass rates and mean scaled scores on the ABPMR initial certifying examinations were compared. MD versus DO degrees and training program 6 years aggregate board pass rates were independent variables. Interventions: Not applicable. Main Outcome Measure: MD and DO pass rates and mean scaled scores on the ABPMR initial certifying examinations. Results: Of the 2187 physicians who were first‐time ABPMR initial certifying examination takers, there were 1596 MDs (73%) and 591 DOs (27%). No statistically significant difference was found in pass rates between MDs and DOs on Part I (94.9% vs. 93.9%, P = .35) or Part II (87.8% vs. 88%, P = .83) of the ABPMR certifying examination. Analysis of mean scaled scores demonstrated higher MD scores on both Part I ( 526, SD = 31, vs. 516, SD = 67, P = .002) and Part II ( 6.73, SD = .83 vs. 6.62, SD = .77, P = .005), significant only in programs with a 90%‐100% pass rate. These differences, however, were of very small magnitude and likely not meaningful from a clinical or educational perspective. Conclusion: This study did not find meaningful differences in performance on the ABPMR certifying examinations between MDs and DOs.